"Die Wiederaufnahme der diplomatischen Beziehungen zwischen Polen und Litauen". F.l.t.r.: ?, Scripa, Koscialkowski
"Die Wiederaufnahme der diplomatischen Beziehungen zwischen Polen und Litauen". F.l.t.r.: ?, Scripa, Koscialkowski.